O2‐independent demethylation of trimethylamine N‐oxide by Tdm of Methylocella silvestris. (20th October 2016) - Zhu, Yijun; Ksibe, Amira Z.; Schäfer, Hendrik; Blindauer, Claudia A.; Bugg, Timothy D. H.; Chen, Yin
Abstract : Bacterial trimethylamine N ‐oxide (TMAO) demethylase, Tdm, carries out an unusual oxygen‐independent demethylation reaction, resulting in the formation of dimethylamine and formaldehyde. In this study, site‐directed mutagenesis, homology modelling and metal analyses by inorganic mass spectrometry have been applied to gain insight into metal stoichiometry and underlying catalytic mechanism of Tdm of Methylocella silvestris BL2. Herein, we demonstrate that active Tdm has 1 molar equivalent of Zn 2+ and 1 molar equivalent of non‐haem Fe 2+ . We further investigated Zn 2+ ‐ and Fe 2+ ‐binding sites through homology modelling and site‐directed mutagenesis and found that Zn 2+ is coordinated by a 3‐sulfur‐1‐O motif. An aspartate residue (D198) likely bridges Fe 2+ and Zn 2+ centres, either directly or indirectly via H‐bonding through a neighbouring H2 O molecule. H276 contributes to Fe 2+ binding, mutation of which results in an inactive enzyme, and the loss of iron, but not zinc. Site‐directed mutagenesis of Tdm also led to the identification of three hydrophobic aromatic residues likely involved in substrate coordination (F259, Y305, W321), potentially through a cation–π interaction. Furthermore, a crossover experiment using a substrate analogue gave direct evidence that a trimethylamine‐alike intermediate was produced during the Tdm catalytic cycle, suggesting TMAO has a dual role of being both a substrate and an oxygen donor for formaldehyde formation. Together, our results provide novel insight into the role of Zn 2+ and Fe 2+ in the catalysis of TMAO demethylation by this unique oxygen‐independent enzyme. Abstract : Trimethylamine N ‐oxide (TMAO) demethylase (Tdm) from Methylocella silvestris contains Zn 2+ and non‐haem Fe 2+ and catalyses an O2 ‐independent demethylation of TMAO, producing dimethylamine (DMA) and formaldehyde (HCHO). Homology modelling and site‐directed mutageneses show that Zn 2+ is coordinated by 3‐Cys. An aspartate residue (D198) likely bridges Fe 2+ and Zn 2+ centres. H276 and H256 contribute to Fe 2+ binding.